CLINICAL AND RADIOGRAPHIC FEATURES OF PATIENTS WITH PRIMARY HIP OSTEOARTHRITIS ACCORDING TO ACR (1991) CRITERIA (Vietnam Journal of Community Medicine, 2026)
Objective: To describe clinical and radiographic features in patients with primary hip osteoarthritis according to ACR (1991) criteria and to analyze associations between clinical features and radiographic findings.Method: Cross-sectional descriptive study of 45 patients (51 hip joints) diagnosed with primary hip osteoarthritis per ACR (1991) criteria at Rheumatology Center of Bach Mai Hospital (July 2024 to August 2025).Results: Most common clinical features were: hip pain during walking (98.0%); functional limitation (60.8%); morning stiffness under 30 minutes (39.2%); pain with hip movement (84.3%); reduced range of flexion, internal rotation, and hip abduction (52.9%). Hip radiographic features: acetabular osteophytes (86.2%); femoral osteophytes (74.5%); subchondral sclerosis (76.5%); joint-space narrowing (58.8%); femoral head deformity (25.5%). The prevalence of Kellgren-Lawrence grades 3-4 was 58.8%. Patients with radiographic hip joint-space narrowing had higher odds of severe pain (VAS ≥ 5) than those without narrowing (OR = 12.8). Compared with Kellgren-Lawrence grades 1-2, those with Kellgren-Lawrence grades 3-4 had much higher odds of functional limitation and decreased range of motion 84 times and 130 times, respectively.Conclusion: Conventional hip X-ray has diagnostic value in determining and classifying the stage of hip osteoarthritis.
Keywords: Hip osteoarthritis, radiography, clinical, VAS.